REHABILITASI ATAU PIDANA? STUDI KRITIS RESTORATIVE JUSTICE PENYALAHGUNAAN NARKOTIKA BERBASIS TEORI PEMIDANAAN INTEGRATIF - Ginta Amelia Cahya; Ali Masyhar; Cahya Wulandari (Fakultas Hukum Universitas Udayana, 2026)
Kajian ini bertujuan untuk menganalisis kerangka regulasi keadilan restoratif di Indonesia, menelusuri landasan teoretis yang menopangnya, serta mengkaji penerapannya dalam penanganan perkara penyalahgunaan narkotika pada tahap penyidikan kepolisian. Metode yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan konseptual, melalui telaah bahan hukum primer, sekunder, dan komparasi hukum. Temuan penelitian mengungkapkan bahwa keadilan restoratif telah mendapatkan legitimasi normatif melalui berbagai instrumen hukum, di antaranya Undang-Undang Sistem Peradilan Pidana Anak, Perpol Nomor 8 Tahun 2021, Peraturan Kejaksaan Nomor 15 Tahun 2020, Perma Nomor 1 Tahun 2024, serta semakin terpadukan dalam KUHP Nasional dan KUHAP (UU No. 20 Tahun 2025). Dari sudut pandang teoretis, orientasi pemidanaan mengalami transformasi dari paradigma retributif ke arah pendekatan yang lebih restoratif dan rehabilitatif, dengan menempatkan pemulihan, keseimbangan sosial, dan reintegrasi pelaku sebagai prioritas. Dalam konteks narkotika, pengguna narkotika dapat diposisikan sebagai korban yang memerlukan rehabilitasi medis maupun psikososial. Meski demikian, penerapan keadilan restoratif di tingkat kepolisian belum berjalan optimal akibat adanya keterbatasan regulasi, ketidakseragaman penafsiran, lemahnya asesmen, koordinasi lintas lembaga yang belum efektif, serta terbatasnya sarana rehabilitasi. Oleh karenanya, diperlukan harmonisasi regulasi, penguatan kapasitas aparat, dan sinergi lintas sektor guna mendukung implementasi yang lebih efektif dan berkelanjutan. This research aims to examine the regulatory framework of restorative justice in Indonesia, to trace the theoretical foundations underlying its application in narcotics offenses, and to analyze its implementation in resolving narcotics criminal cases at the police level. A normative juridical approach is applied, combining statutory and conceptual analyses of primary and secondary legal sources along with comparative legal studies. The findings reveal that restorative justice has gained normative grounding through multiple legal instruments, including the Juvenile Criminal Justice System Law, Police Regulation Number 8 of 2021, Prosecutor Regulation Number 15 of 2020, and Supreme Court Regulation Number 1 of 2024, and has been progressively embedded in the newly enacted Criminal Code (KUHP) and Criminal Procedure Code (KUHAP). From a theoretical standpoint, the philosophy of punishment has undergone a fundamental shift away from a retributive orientation toward more integrative, restorative, and rehabilitative objectives, centering on recovery, social equilibrium, and the offender’s reintegration into society. In the specific context of narcotics enforcement, the application of Restorative Justice carries distinct characteristics, given that drug abusers are regarded as victims of dependency who require medical and social rehabilitation rather than punitive measures. Nonetheless, its implementation at the police level remains suboptimal. This is illustrated by the contrasting outcomes of two cases: the Rambu case, where restorative justice was successfully applied, and the Iman case, where procedural and institutional constraints prevented its use. These disparities are attributable to regulatory gaps, inadequate assessment mechanisms, diverging interpretations among law enforcement personnel, limited inter-agency coordination, and insufficient rehabilitation infrastructure. Consequently, regulatory harmonization, capacity-building among law enforcement, and stronger cross-sectoral cooperation are essential to ensure that Restorative Justice in Indonesia is implemented effectively and sustainably.